Whole genomes from Angola and Mozambique inform about the origins and dispersals of major African migrations - Tallman, Sam; Sungo, Maria das Dores; Saranga, Sílvio; Beleza, Sandra (Nature communications, 2023)
As the continent of origin for our species, Africa harbours the highest levels of diversity anywhere on Earth. However, many regions of Africa remain under-sampled genetically. Here we present 350 whole genomes from Angola and Mozambique belonging to ten Bantu ethnolinguistic groups, enabling the construction of a reference variation catalogue including 2.9 million novel SNPs. We investigate the emergence of Bantu speaker population structure, admixture involving migrations across sub-Saharan Africa and model the demographic histories of Angolan and Mozambican Bantu speakers. Our results bring together concordant views from genomics, archaeology, and linguistics to paint an updated view of the complexity of the Bantu Expansion. Moreover, we generate reference panels that better represents the diversity of African populations involved in the trans-Atlantic slave trade, improving imputation accuracy in African Americans and Brazilians. We anticipate that our collection of genomes will form the foundation for future African genomic healthcare initiatives. African human genome variation remains under-sampled. Here, the authors present a collection of 350 whole genome sequences from Angola and Mozambique and model the timing and extent of significant demographic events in African history.